Output-Feedback Nonlinear Adaptive Control Strategy of Three-phase AC/DC Boost Power Converter for On-line UPS Systems. Issue 13 (2016) - Kissaoui, M.; Al Tahir, A.A.R.; Abouloifa, A.; Chaoui, F.Z.; Abouelmahjoub, Y.; Giri, F.
Abstract: In this paper, the problem of controlling three-phase boost power converter is considered for charging the battery in uninterruptible power supply (UPS) systems. The control objective is twofold: (i) ensuring a satisfactory power factor correction (PFC) at the grid-UPS connection; (ii) guaranteeing a tight regulation of the DC output voltage despite of load uncertain. The considered control problem entails several difficulties including: (i) the numerous state variables that are inaccessible to measurements; (ii) the uncertainty that prevails on some system parameters. The problem is dealt with using a cascade nonlinear adaptive controller that is developed making use of the Lyapunov control design technique. The inner-loop ensures the PFC objective and involves an adaptive observer estimating the grid phase currents, the magnitude of the parameters grid phase voltages and the load resistance. The estimation is only based on the online measurements of DC output voltage. The outer-loop regulates the DC output voltage up to small size ripples.